Perbandingan Latihan Rondos Dengan Circle Passing Drill Terhadap Akurasi Passing Pada Futsal MAN 1 Tangerang Selatan - Foggy Abed Al Billal; Andri Irawan; Bambang Kridasuwarso (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research aims to determine, 1) increasing Passing accuracy through the Rondos training method, 2) increasing Passing accuracy using the Circle Passing Drill training method, 3) the difference in increasing Passing accuracy using the Rondos training method and Circle Passing Drill. This research method uses an experimental method with research using a two groups "pre-test and post-test design." The subjects of this research were 24 MAN 1 South Tangerang student futsal athletes taken using a purposive sampling technique. Data collection was carried out by carrying out a Passing accuracy test at a distance of 18 meters using a small goal and 10 kicks for each athlete. Data analysis was carried out using the dependent and independent "t test" with a significance level of 0.5. Research results: 1) training using Rondos, obtained t count of 10 greater than t table 2.201, so it means that H0 is rejected and H1 is accepted, meaning there is a significant increase, 2) training using Circle Passing Drill, obtained t count of 5.5 is greater from t table 2.201, then H0 is rejected and H1 is accepted, meaning there is a significant increase, 3) comparing the final test results of the two training methods, the results obtained are, t count 2.8 is greater than t table 2.074, meaning there is a difference between the training methods Rondos using the Circle Passing Drill training method. So it can be concluded that there is a significant change in Rondos training with an average of 6.5 and the results of Circle Passing Drill training with an average of 5.5.